2022
DOI: 10.3892/mmr.2022.12672
|View full text |Cite
|
Sign up to set email alerts
|

Co‑expressed microRNAs, target genes and pathways related to metabolism, inflammation and endocrine function in individuals at risk for type 2 diabetes

Abstract: Micrornas (mirnas) may be considered important regulators of risk for type 2 diabetes (T2d). The aim of the present study was to identify novel sets of mirnas associated with T2d risk, as well as their gene and pathway targets. circulating mirnas (n=59) were measured in plasma from participants in a previously completed clinical trial (n=82). an agnostic statistical approach was applied to identify novel sets of mirnas with optimal co-expression patterns. In silico analyses were used to identify the messenger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The gene targets and miRNAs identified in this review mostly differ from those that have been previously emphasized for T1D and T2D, suggesting a distinct pathophysiology for GDM ( 76 78 ). Some exceptions are miR-16-5p ( 43 ), miR-29a-3p, miR-146a, miR-182, and miR-342-3p as previously mentioned in section 4.7 ( 18 , 31 34 , 36 , 37 , 43 , 70 , 76 , 77 , 79 , 80 ). MiR-29a-3p was reported with mixed results in both GDM and T2D studies, with one or more study showing it to be upregulated and one or more showing it to be downregulated compared with controls.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The gene targets and miRNAs identified in this review mostly differ from those that have been previously emphasized for T1D and T2D, suggesting a distinct pathophysiology for GDM ( 76 78 ). Some exceptions are miR-16-5p ( 43 ), miR-29a-3p, miR-146a, miR-182, and miR-342-3p as previously mentioned in section 4.7 ( 18 , 31 34 , 36 , 37 , 43 , 70 , 76 , 77 , 79 , 80 ). MiR-29a-3p was reported with mixed results in both GDM and T2D studies, with one or more study showing it to be upregulated and one or more showing it to be downregulated compared with controls.…”
Section: Discussionmentioning
confidence: 95%
“…A prior study conducted by Flowers et al. (2022) assessed pathways targeted by differentially expressed miRNAs in people at risk for T2D and identified three themes (i.e., metabolism and inflammation, endocrine, and hormone) ( 43 ). Many of the implicated pathways identified by the studies included in this review also fit within these themes.…”
Section: Discussionmentioning
confidence: 99%
“…A useful feature of the most cited databases gives the user the option to download the validated data, making it easy to manipulate further in programs such as R. The download feature was applied to this review, which allowed us to identify with certainty the total numbers of the miRNAs and genes included. Regarding citations, frequent use by the scientific community suggests that those tools are user-friendly and intuitive ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…RFXANK mutations are prevalent in bare lymphocyte syndrome (BLS) group B, an immunodeficiency disorder affecting CD4+ T and B cells [ 50 ]. However, RFXANK has not been associated with obesity or T2D in previous studies, though MHCII has been found to play a role in obesity [ 51 ], and our own prior studies have identified pathways related to inflammation and immunity as common themes in individuals at risk for T2D [ 52 ]. Deng et al [ 51 ] analyzed RFXANK between 7 obese women and 7 lean postmenopausal women but did not find the expression to be significantly different.…”
Section: Discussionmentioning
confidence: 99%